Identifikasi Bakteri Mirip Coliform pada Media Cromocoult Coliform Agar (CCA) - Evriarti, Paulina Rosa (Jurnal Laboratorium Khatulistiwa, 2022)
Coliform-like bacteria can be found when examining coliforms in fresh water using the CCA media on membrane filter method. Therefore, it is necessary to characterize and identify coliform-like colonies that grow on CCA medium so that is easier to perform colony count analysis. One hundred ml of fresh water samples were filtered using filter membrane paper and then planted in CCA medium. Two different colonies growing on the media (red (A) and pink-purple (B)) were subjected to oxidase test, gram staining and re-cultured in various growth media such as blood agar, nutrient agar, MacConkey, and B. coli agar. Both colony types were also identified with Vitek MS to determine the species. The results of the examination showed that the red colonies (code A) were coliform-like bacteria, while the pink-purple colonies (code B) were coliform bacteria. The characteristics of coliform-like bacteria are that they produce hemolysis on blood agar and do not ferment lactose. Identification with Vitek MS showed that the isolated coliform-like bacteria was Aeromonas hydrophilla. Therefore, it can be concluded that Aeromonas sp. are coliform-like bacteria that grow on CCA, so further verification is needed when counting membrane filter colonies using CCA media.